2020
DOI: 10.1097/pcc.0000000000002484
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Framework Using Remote Telesimulation With Standardized Parents to Improve Research Staff Preparedness for Informed Consent in Pediatric Critical Care Research*

Abstract: Objectives: The Heart And Lung Failure—Pediatric INsulin Titration study was experiencing poor subject enrollment due to low rates of informed consent. Heart And Lung Failure—Pediatric INsulin Titration investigators collaborated with the Perelman School of Medicine Standardized Patient Program to explore the novel use of telesimulation with standardized parents to train research staff to approach parents of critically ill children for informed consent. We describe the feasibility, learner acceptan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The telesimulation curriculum presented in this article has been successfully applied to learners ( n = 2989) with minimal disruption and/or technical difficulties; however, it is important to highlight the fact that telesimulation in the format presented in this paper is time-consuming and more expensive than conducting in-person simulations. Other studies and reports on telesimulation have underlined its feasibility and proposed it as a low-cost alternative to provide training during the pandemic [ 13 ]; however, our experience suggests that telesimulation could become quite expensive with large student cohorts (more than 250 learners). The requirements to ensure active and engaged participation of the learners during telesimulation, such as small 6–8 student groups (compared to our typical 15–20 student groups during our in-person simulation), as well as the need for personal backup able to react quickly in case of technical or connection difficulties, all contribute to the necessity of securing appropriate resources.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…The telesimulation curriculum presented in this article has been successfully applied to learners ( n = 2989) with minimal disruption and/or technical difficulties; however, it is important to highlight the fact that telesimulation in the format presented in this paper is time-consuming and more expensive than conducting in-person simulations. Other studies and reports on telesimulation have underlined its feasibility and proposed it as a low-cost alternative to provide training during the pandemic [ 13 ]; however, our experience suggests that telesimulation could become quite expensive with large student cohorts (more than 250 learners). The requirements to ensure active and engaged participation of the learners during telesimulation, such as small 6–8 student groups (compared to our typical 15–20 student groups during our in-person simulation), as well as the need for personal backup able to react quickly in case of technical or connection difficulties, all contribute to the necessity of securing appropriate resources.…”
Section: Methodsmentioning
confidence: 96%
“…Part of the in-person SPs simulation program for medical undergraduate students at the University of Montreal was modified and adapted to meet the logistic and learning requirements for a new telesimulation curriculum. Unlike most of the experiences documented in the literature, which describe the use of mannequin-based telesimulation to train technical skills at a distance, the competencies of the telesimulation program reported in this paper focused on communication skills for which the SP method was adopted [ 13 ]. The main objective of the telesimulation curriculum described here was to provide communication and clinical reasoning skills training for first, second, and third-year medical students during the COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that eIC provides location exibility by allowing researchers to obtain informed consent from prospective research participants in an online format, such as remote videoconferencing, rather than being limited to taking place onsite [46]. The remote eIC can improve the recruitment e ciency for some clinical investigations and reduce the costs of travel and time [25]. In a randomized trial of patients with emergent large vessel occlusion strokes, eIC streamlined the consenting process by reducing distance and time [47].…”
Section: Knowledge Of Electronic Informed Consentmentioning
confidence: 99%
“…In terms of studies on subjects, for example, many scholars in the United States have conducted studies on one or more of these aspects of eIC, such as recruitment rate[18], information informativeness [19], understanding [20,21], satisfaction [22,23], and participation decision [24]. A survey of medical researchers found that pediatric critical care researchers had a positive attitude toward the usability of eIC [25]. However, a study has shown that some clinical trial researchers may not consider using eIC in the future [26].…”
Section: Introductionmentioning
confidence: 99%